Variation of loads on a three-bladed horizontal axis tidal turbine with frequency and blade position. (November 2018) - Payne, Grégory S.; Stallard, Tim; Martinez, Rodrigo; Bruce, Tom
Abstract: Sustainable and cost effective design for tidal current turbines requires knowledge of the complex nature of unsteady loads on turbine components including blades, rotor and support structure. This study investigates experimentally the variation with frequency of rotor thrust and torque loads, of streamwise root bending moment on individual blades and of loads on foundation at the bed. Comparisons between these different load spectra are also established. The impact of absolute rotor angular position on blade and rotor thrust loads is also examined. The study is based on measurements from a 1/15 scale, three-bladed, horizontal axis machine tested in a recirculating flume, in onset flows of 3% and 12% turbulence intensity. It is found that for frequencies below the rotational frequency, load spectra are correlated to spectral density of the onset flow velocity. Above the rotational frequency, loads are mainly affected by turbine operation phenomena. The tower shadowing effect is clearly identified through frequency and angular analysis. Finally, thrust loads as experienced by the rotor alone are for the first time compared with streamwise and transverse foundation loads. Higher frequency loads experienced by the tower are shown to be affected by different vortex shedding regimes associated with different regions of the wake. All the experimental measurements presented in this article can be accessed fromhttp://dx.doi.org/10.7488/ds/2423 .